2013
DOI: 10.1248/cpb.c12-01024
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Diosgenin-Ibuprofen Derivatives and Their Activities against Insulin-Dependent Diabetes Mellitus

Abstract: The synthesis and anti-diabetes activities of diosgenin-ibuprofen derivatives were investigated. Ibuprofen (IBU) was chemically coupled with diosgenin either directly or through amino acid esters linkers. The effects of these compounds on lipopolysaccharide (LPS)-induced nitric oxide (NO) generation were assessed. The results showed spirost-5-en-3β-yl (2-(4-isobutyl-phenyl)-propionate) (4) was of better activity to suppress the production of NO in the supernatant of LPS-stimulated RAW264.7 cells. In vivo inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Hence, n-(phenyl) methyl substitution in DG has strong anti-inflammatory, antioxidant and anti-Aβ activity 69 . Ibuprofen (2-(4-isobutylphenyl)-propionic acid) combined with DG derivatives employing 6-aminohexanoic acid at the 27th position has substantially proven for its anti-inflammatory activity in in-vitro and in-vivo inflammatory models 70 .…”
Section: Structure Activity Relationship (Sar) Anti-inflammatorymentioning
confidence: 99%
“…Hence, n-(phenyl) methyl substitution in DG has strong anti-inflammatory, antioxidant and anti-Aβ activity 69 . Ibuprofen (2-(4-isobutylphenyl)-propionic acid) combined with DG derivatives employing 6-aminohexanoic acid at the 27th position has substantially proven for its anti-inflammatory activity in in-vitro and in-vivo inflammatory models 70 .…”
Section: Structure Activity Relationship (Sar) Anti-inflammatorymentioning
confidence: 99%
“…It has been reported that DG shows vasodilatory activity [5], renoprotective effects [6]. DG derivatives are known for the wide spectrum of biological activities, such as to prevent thrombosis effects [7], anti-inflammatory activity [8], anti-cancer activity [9]. Moreover, many steroid sapogenins such as diosgenin, sisalagenin, neo-pentologenin and luvigenin have already been used in many aspects for the treatment of various diseases.…”
Section: Commentmentioning
confidence: 99%